The Academic Avant-Garde : Poetry and the American University - Andrews, Kimberly Quiogue, 1983- (Book collections on Project MUSE., 2023)
From this dialectical (and sometimes polemical) standpoint, The Academic Avant-Garde reframes major characteristics of contemporary experimental literature, opens up new ways of thinking about the relationship between creative writing and literary study, and expands the horizon of possibility for engaging with and teaching the history of poetry.